2020
DOI: 10.1186/s12877-020-01638-0
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol for a hospital-to-home transitional care intervention for older adults with multiple chronic conditions and depressive symptoms: a pragmatic effectiveness-implementation trial

Abstract: Background: Older adults (> 65 years) with multiple chronic conditions (MCC) and depressive symptoms experience frequent transitions between hospital and home. Care transitions for this population are often poorly coordinated and fragmented, resulting in increased readmission rates, adverse medical events, decreased patient satisfaction and safety, and increased caregiver burden. There is a dearth of evidence on best practices in the provision of transitional care for older adults with MCC and depressive sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 66 publications
1
17
0
Order By: Relevance
“…Further details on patient engagement within ACHRU 22 and 1 of the 17 projects has been published elsewhere. 22 , 35 , 36 …”
Section: Resultsmentioning
confidence: 99%
“…Further details on patient engagement within ACHRU 22 and 1 of the 17 projects has been published elsewhere. 22 , 35 , 36 …”
Section: Resultsmentioning
confidence: 99%
“…Pragmatic features included the recruitment of participants representative of the population presenting in the hospital setting, the flexible delivery of the intervention by Registered Nurses (RNs) from the setting, the use of patient-relevant outcomes (e.g., quality of life, patient experience), and the use of intention-to-treat analysis. Details of the study design and outcome measures are reported in the published study protocol [71]. The methods, results, and flow of participants through the study are presented here according to the CONSORT statement for pragmatic randomized controlled trials [70].…”
Section: Methodsmentioning
confidence: 99%
“…Details regarding the CAST intervention are described in the published study protocol [71]. The intervention was developed using the Medical Research Council Framework for developing complex interventions, which highlights the importance of theoretical and empirical evidence [75].…”
Section: Interventionmentioning
confidence: 99%
See 2 more Smart Citations